Contribution of Groundwater to River Discharge in the Mampang Sub-watershed - Riana Palupi; Agus M. Ramdhan; Rusmawan Suwarman (GoAcademica Research & Publishing, 2023)
Water is a necessity of human life. In fulfilling this need, the use of groundwater is often used. Groundwater is a non-renewable resource. Jakarta is a city traversed by many rivers and has a morphological dependence on the upstream watershed (DAS) in the Jabodetabek Region. The research location is in the Mampang Sub-watershed, which is in the Jakarta and Depok areas. The Mampang sub-watershed is geographically located at 106°48'44